Barriers to Palliative Kader in Assisting Cancer Patients and Families at Home - Hermawan, Stepanus Maman; Wihardja, Hany (Indonesian Journal of Global Health Research, 2024)
Palliative care programs are important to improve the quality of life of patients and families in the face of life-threatening disease problems through prevention and alleviation of symptoms. This research aims to explore the barriers of palliative kader’s in providing care and assistance to cancer patients and families. This qualitative research is using a descriptive method. The sampling technique in this study was the purposive sampling technique. Participants in this study were 10 palliative kader in the DKI Jakarta area who provided services in the form of care and assistance to cancer patients and families, data collection techniques using in-depth interviews. Four themes emerged in the form of (1) lack of family support, (2) inadequate health promotion media, (3) lack of support system for palliative kader’s, and (4) lack of confidence in the care and assistance of cancer patients and families. This study emphasizes the importance of adaptive coping mechanisms for patients and families so that they can support palliative kader in care and assistance in the form of meeting basic needs. Empowerment increases the ability of palliative kader’s through training to strengthen the duties and roles of kader and coordinate with relevant stakeholders who can accommodate the solution of any obstacles experienced by palliative kader.